İktisadi güvenliğin eleştirel politik iktisadı : Hegemonik ABD-Birleşik Krallık örneklerine sistemsel bir yaklaşım (1873-2008) - Taşkıran, Doğukan (My University, 2023)
Bu çalışma kapsamında 2008 krizinden sonra giderek ağırlaşan iktisadi şartlar karşısında uluslararası kurumların ve devletlerin resmi söylemlerinde yer edinmeye başlayan iktisadi güvenlik konsepti, eleştirel bir perspektiften incelenmektedir. Günümüzdeki ağır tarihsel ve iktisadi şartlar yalnızca tesadüfen beliren olaylar olarak kalmamakta, modern iktisadın gelişiminde döngüsel şekilde ortaya çıkan bunalımlar ile krizlerin yeni bir boyutunu temsil etmektedir. Literatürde bu kapsamda iktisadi güvenlik konseptinin açıklaması genellikle onun ne olması gerektiği üstüne yoğunlaşırken güvenliğin iktisadi boyutundan söz etme nedenimiz, sosyal ve tarihsel kaynaklarının ne olduğu yeterince tartışılmamıştır. Diğer bir deyişle, iktisadi güvenliğe dair tartışmalar epistemolojik bir zeminde vuku bulmuşken bu çalışma meselenin ontolojik yönüne odaklanmayı ve onu eleştirel bir biçimde açıklamayı amaçlamaktadır. Kavramsal tartışma özellikle ekonomiyi güvenlik ilişkilerinden soyutlayarak politik kaynaklarını ele almamaktadır. Bunun yanında güvenliğin toplumla olan ilişkisinde güvenlik bölüşümünden güvenliğin etkilerine kadar bir dizi sorun, toplumun yapısından azade bir şekilde ele alınmaktadır. Eleştirel teori, toplumun parçalı yapısına odaklanırken farklılaşmış toplumsal aktörlerin güvenlikle olan ilişkisini incelemektedir. Çalışmadaki iddia edilen hipotezde iktisadi güvenlik, dünya pazarına bağlı uluslararası iktisadi sistemin çelişkilerinden doğmakta, devletlerin tepkileri ise sistemin doğurduğu bunalım ve krizlerin etkisine göre şekillenmektedir. Bu hususta kendi hegemonik dönemlerinde Birleşik Krallık ve Amerika Birleşik Devletleri’nin tarihsel konumları ayrı ayrı incelenmektedir. Sonucunda ABD-Birleşik Krallık örneklerinde incelenen çeşitli tarihsel değişkenlere göre krizler ve bunalımlar uluslararası sistemde kendiliğinden doğmakta, ancak politik kararlarla çözülebilecek güvenlik sorunları meydana getirmektedir.

I analyze the concept of economic security, which started to take place in the formal discourses of international institutions and states in the presence of gradually worsening post-2008 crisis, within the context of this study from a critical perspective. The severe historical and economic circumstances of today are not incidental events, but also represents a new dimension of depressions and crises which occur cyclically in the development of modern economy. While the explanation of the concept of economic security in this context in the literature generally focuses on what the concept should be, the reason why we talk about the economic dimension of security and what its social and historical sources are is not adequately discussed. In other words, while the debates on economic security progressed on an epistemological ground, this study aims to focus on the ontological aspect of the issue and to explain it critically. Conceptual debate does not specifically address the political sources of economy by isolating it from security relations. While critical theory focuses on the fragmented structure of society, it analyzes the relations of differentiated social actors with security. According to main hypothesis of this study, economic security arises from the contradictions of international economic system which is related with world market and reactions of states are shaped according to impacts of the depressions and crises caused by the system. In this respect, the historical positions of the United Kingdom and the United States of America in their hegemonic periods are examined separately. Consequently, according to various historical variables examined in US-UK examples, crisis and depressions spontaneously arise in the international system and generate security problems that can be only solved by political decisions.
Keywords: According to main hypot-hesis of this study; according to various historical variables examined in US-UK examples; Amerika Birleşik Devletleri; Birleşik Krallık; bunalım; but also represents a new dimension of depressions and crises which occur cyclically in the development of modern economy; Conceptual debate does not specifically address the political sources of economy by isolating it from security relations; Consequ-ently; crisis and depressions spontaneously arise in the international system and generate security problems that can be only solved by political decisions; economic security arises from the contradictions of international economic system which is related with world market and reactions of states are shaped according to impacts of the dep-ressions and crises caused by the system; Ekonomi; eleştirel; eleştiri; emek I analyze the concept of economic security; güvenlik; In other words; In this respect; International economic relations; it analyzes the relations of differentiated social actors with security; kriz; Political aspects; sermaye; Siyasal açıdan; tarih; teori; the historical positions of the United King-dom and the United States of America in their hegemonic periods are examined separately; the reason why we talk about the economic dimension of security and what its social and historical sour-ces are is not adequately discussed; The severe historical and economic circumstances of today are not incidental events; this study aims to focus on the ontological aspect of the issue and to explain it critically; Uluslararası ekonomik ilişkiler; United Kingdom; United States; which started to take place in the formal discourses of international institutions and states in the presence of gradually worsening post-2008 crisis; While critical theory focuses on the fragmented structure of society; while the debates on economic security progressed on an epistemological ground; While the explanation of the concept of eco-nomic security in this context in the literature generally focuses on what the concept should be; within the context of this study from a critical perspective